Pacific Youth Strategy 2010 : youth empowerment for a secure, prosperous and sustainable future (Secretariat of the Pacific Community [S.l.]NC, 2006)
Seeks to prepare young people in the Pacific Region to take responsibility for their overall development and well-being. Represents a firm commitment to providing more opportunities for young Pacific Islanders so that they will be inspired to realise their full potential and contribute to the social, economic and cultural well-being of their societies.
Keywords: YOUTH